Exploiting the Degradation Mechanism of NCM523 || Graphite Lithium‐Ion Full Cells Operated at High Voltage. Issue 2 (29th December 2020) - Klein, Sven; Bärmann, Peer; Beuse, Thomas; Borzutzki, Kristina; Frerichs, Joop E.; Kasnatscheew, Johannes; Winter, Martin; Placke, Tobias
Abstract: Invited for this month′s cover is the group of Tobias Placke and Martin Winter at the MEET Battery Research Center (University of Münster). The image shows the failure mechanism of high‐voltage operated NCM523 || graphite lithium‐ion cells, that is, the dissolution of transition metals (Mn, Co, Ni) from the NCM523 cathode and subsequent deposition at the graphite anode, resulting in formation of Li metal dendrites. The Full Paper itself is available at 10.1002/cssc.202002113 . Abstract : "The high‐voltage operation of NCM || graphite LIB cells is a severe challenge…" This and more about the story behind the research that inspired the Cover image is presented in the Cover Profile. Read the full text of the corresponding research at 10.1002/cssc.202002113 . View the Front Cover here: 10.1002/cssc.202002871 .